Preparation method of silk fibroin composite freeze-drying filler with controllable molecular weight
By using controllable molecular weight silk fibroin, non-specific stabilizers, microspheres and microsphere dispersion carriers, combined with lyophilization technology, a composite hydrophobic filler was prepared, which solved the problems of poor moisturizing and cumbersome combination of existing hydrophobic preparations, and achieved long-term skin improvement and convenience of use.
Patent Information
- Application Number
- CN202411993876.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing hydroluminescent preparations have limited effects in moisturizing and moisturizing, short maintenance time, and cumbersome compounding process, which affects the convenience of use, and there is a risk of allergic reactions and skin damage.
Using controllable molecular weight silk fibroin, non-specific stabilizers, microspheres and microsphere dispersion carriers, composite fillers are prepared through lyophilization technology to ensure uniform dispersion of microspheres, reduce the risk of agglomeration and nodules, and improve redissolution time and user experience.
It achieves long-term moisturizing and moisturizing effects, improves skin tone, brightens and whitens, shrinks pores, lightens spots, removes acne and sterilizes wrinkles, and improves product stability and convenience of use.
Smart Images

Figure CN119746158A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of freeze-dried preparations, and in particular to a method for preparing a controllable molecular weight silk fibroin composite freeze-dried filler. Background Art
[0002] The suppleness of the epidermis is closely related to the sodium hyaluronate content of the subcutaneous tissue. Due to photoaging or normal aging, sodium hyaluronate is continuously lost from the body, weakening the skin's ability to retain moisture, causing dryness and even wrinkles. Hydrating injections are a form of "mesotherapy." Hydrating preparations are compounded into a solution and then injected into the injection site, typically in the superficial to mid-dermis, to achieve hydration and moisturizing effects.
[0003] Although the common hydrating preparations can play a role in hydrating and moisturizing to a certain extent, they are limited by their respective technical characteristics and process preparation characteristics, and it is difficult to fully meet the comprehensive needs of users. For example, although the low molecular weight sodium hyaluronate hydrating injection injection takes a short time to compound and the compounded solution is relatively uniform, its hydrating and moisturizing effect in the body is too short (less than 1 month, short-term hydrating), and it only provides hydration, and does not have the function of long-term micro-area filling and repair. This leads to the need for users to frequently perform hydrating injections, which invisibly increases the various costs of users. The high molecular weight / cross-linked sodium hyaluronate hydrating injection injection has a longer maintenance time in the body and a better hydrating and moisturizing effect, which can meet user needs to a certain extent. However, due to its long compounding time, its convenience in actual use is greatly limited. Collagen hydrating products do not have significant hydrating and moisturizing effects because their main function is only to increase skin thickness and elasticity. Allergic reactions and skin redness and swelling are relatively common after collagen injection. Microsphere hydrating injections can stimulate collagen regeneration in the body, but because their compounding takes too long and is prone to uneven re-dissolution and even agglomeration effects during the compounding process, there is a risk of clinical nodules after use.
[0004] For users who need hydration, they often also have comprehensive skin problems such as dull skin tone, large pores, chloasma, true wrinkles, acne, red blood vessels, etc., which require combined treatment.
[0005] Furthermore, with age, the various active ingredients in the extracellular matrix (ECM) show a significant decrease, indicating signs of aging. However, the ECM is not composed of a single component; its complex composition, arrangement, and structure form a microenvironment. This dynamically changing microenvironment not only provides traditional physical support but also serves as a biomechanical fulcrum for controlling stem cell behavior.
[0006] Therefore, the starting point of this invention (inventing a long-lasting water light) is to find a multifunctional comprehensive composite material with good biocompatibility that can not only maintain the hydration and moisturizing effect for a long time, but also stimulate collagen regeneration in an appropriate amount, and compensate for the loss of extracellular matrix. In addition, considering that most water light treatments require compounding into a solution and then injecting it, when developing such a comprehensive composite material, it is necessary to take into account the convenience of the compounding process.
[0007] As a natural polymer material, silk fibroin has broad application prospects in biomedicine, tissue engineering, and controlled drug release due to its excellent biocompatibility, degradability, and mechanical properties. Microspheres can induce an immune response within tissues, inducing fibroblasts to regenerate dermal matrix components such as collagen and elastic fibers, thereby inducing collagen regeneration in the skin.
[0008] Silk fibroin exists primarily as random coils in aqueous solution, but this structure is not thermodynamically stable. Under certain external conditions (such as temperature changes, pH changes, etc.), the random structure will transform into a β-pleated structure, causing the silk fibroin to form a gel or precipitate. This characteristic makes silk fibroin solutions prone to precipitation problems during storage and transportation. Moreover, under unsuitable conditions, silk fibroin may be difficult to dissolve or easily form precipitates after dissolution. In addition, the large molecular weight of silk fibroin also increases its difficulty in dissolving. Because silk fibroin solutions are extremely susceptible to deterioration when the environment changes, their storage time at room temperature is too short. During transportation, if there is shock or temperature changes, the silk fibroin solution is likely to form a gel state, thereby affecting its effectiveness. This makes the transportation of silk fibroin solutions difficult.
[0009] Medical aesthetic injections of microsphere fillers also carry numerous risks. For example, existing freeze-dried microsphere-containing hydrating products are typically dissolved in saline solution before compounding, which typically takes more than 5 minutes. This long compounding process results in a poor customer experience. Directly compounding with saline solution can also lead to uneven dispersion of the microspheres during the injection process, compromising the uniformity and effectiveness of the product. Furthermore, uneven dispersion can cause localized overabsorption or accumulation of the fillers, potentially damaging the skin and causing side effects such as redness, swelling, and localized induration. If injected improperly, the filler can enter blood vessels, causing serious complications such as vascular embolism, thereby compromising the overall cosmetic effect.
[0010] To address the aforementioned complex clinical needs and numerous process challenges, this patent utilizes specific nonspecific stabilizers to address the difficulties of silk fibroin with varying molecular weights, including poor solubility, precipitation, and transport. A one-step molding method overcomes the shortcomings of traditional microsphere preparation, ensuring uniform distribution of microspheres within the microsphere dispersant and reducing the risk of agglomeration and nodules during injection. Finally, freeze-drying technology effectively improves the product's texture and appearance, significantly shortening reconstitution time and enhancing the user experience.
[0011] This multifunctional comprehensive composite freeze-dried filler can not only fully meet the basic functions of hydrating and moisturizing after compounding and injection, but also create matrix conditions for the repair of the entire microenvironment, and effectively improve skin tone, brighten and whiten, shrink pores, fade spots, remove acne and sterilize, and improve wrinkles. Summary of the Invention
[0012] To address these challenges, the present invention provides a method for preparing a controllable molecular weight silk fibroin composite freeze-dried filler. This method utilizes a specific freeze-drying process, a nonspecific stabilizer, microspheres, and a microsphere dispersion carrier to ensure good microsphere dispersion. The silk fibroin composite freeze-dried filler is convenient to store, transport, and use, and has a long shelf life.
[0013] The preparation method of the controllable molecular weight silk fibroin composite freeze-dried filler of the present invention comprises:
[0014] S1: Mix the silk fibroin solution and the non-specific stabilizer to prepare a composition liquid A; S2: S3: Mix the composition liquid A and the composition liquid B to obtain a freeze-dried composition liquid; S4: Pre-cooling and forming; S5: Freeze-drying.
[0015] Further
[0016] S1: preparing composition solution A: adding a nonspecific stabilizer to silk fibroin solutions of different molecular weights (protein concentration is 1 mg / mL-50 mg / mL) and mixing; the silk fibroin has a narrow distribution and controllable molecular weight, and the molecular weight range is 10 kDa-80 kDa, 80 kDa-100 kDa, 100 kDa-120 kDa, 120 kDa-160 kDa, 160 kDa-200 kDa, and >200 kDa;
[0017] S2: Preparation of composition liquid B: adding purified water to the microsphere dispersion carrier and microspheres for swelling;
[0018] S3: adding component liquid A to component liquid B, swelling and mixing at low temperature, to prepare the final freeze-dried component liquid;
[0019] S4: Pre-cooling of freeze-dried components: For pre-cooling, select one of S4.1 or S4.2.
[0020] S4.1 Pre-cooling into a specific shape: Pre-cool the prepared freeze-dried composition liquid into a specific shape; preferably, the freeze-dried composition liquid is 15 to 45 μL; preferably, the volume of the specific shape is within 5.00 mm 3 -40.00mm 3 The shape includes but is not limited to sphere, square, five-pointed star shape, and is preferably spherical.
[0021] S4.2 Pre-cooling to form fibers: Pour the freeze-dried composition into a container, and place the container filled with the freeze-dried composition into a refrigerator for pre-cooling to form fibers; the container is preferably a vial; the amount of freeze-dried composition used is 1-3 g;
[0022] S5: Place the pre-cooled pellets in a freeze dryer for freeze drying.
[0023] Furthermore, in step S1, the mass ratio of silk fibroin to nonspecific stabilizer is 1.5-8:1-3, and the nonspecific stabilizer includes one or more of I, II, III, and IV, and specific examples are as follows:
[0024] Ⅰ: Sugar substances such as trehalose, lactose, sucrose, maltose, caramel
[0025] Ⅱ: Sugar alcohols such as mannitol, sorbitol, xylitol, erythritol
[0026] Ⅲ: Polyols such as glycerol, ethylene glycol, butanediol
[0027] IV: Cellulose derivatives such as sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose
[0028] Furthermore, in step S1, the molecular weight of the silk fibroin solution (protein concentration is 1 mg / mL-50 mg / mL) is 10 kDa-80 kDa, 80 kDa-100 kDa, 100 kDa-120 kDa, 120 kDa-160 kDa, 160 kDa-200 kDa, and >200 kDa.
[0029] Furthermore, in step S2, the mass ratio of microspheres: microsphere dispersion carrier (microsphere dispersant concentration is 1 mg / mL-40 mg / mL): purified water = 1-3: 50-100: 500-1000, the microspheres are the substance shown in VII, and the microsphere dispersant is the substance shown in VIII:
[0030] VII: Microspheres are divided into natural polymer microspheres and synthetic polymer microspheres
[0031] Natural polymer microspheres such as starch microspheres, albumin microspheres, gelatin microspheres, chitosan
[0032] Synthetic polymer microspheres such as polylactic acid microspheres, hydroxyapatite microspheres, polycaprolactone microspheres
[0033] VIII: Microsphere dispersion carriers such as sodium hyaluronate, sodium hyaluronate, sodium polyglutamate
[0034] Furthermore, in step S3, when component liquid A is added to component liquid B, it needs to be slightly shaken while adding. After complete addition, it is placed in a refrigerator at 2-8°C for 8 to 24 hours to swell until it is completely dispersed.
[0035] Furthermore, in step S4, freeze-dried pellets are formed by dropping the freeze-dried component solution (15-45 μL) into liquid nitrogen, wherein the volume of each freeze-dried pellet is 5.00 mm 3 -40.00mm 3 The freeze-dried fiber is made by dropping the freeze-dried composition liquid (1-3g) into a vial, and then pre-cooling the vial containing the freeze-dried mixture in a -18℃ refrigerator. The volume of each bottle of freeze-dried fiber is 1cm 3 -3 cm 3 .
[0036] A controllable molecular weight silk fibroin composite freeze-dried filler is prepared by adopting the above-mentioned preparation method.
[0037] The above-mentioned composite freeze-dried product specifically includes: the volume of the freeze-dried ball is 5.00mm 3 ~40.00mm 3 The particle size is 1-5 mm, and the surface roundness of the freeze-dried ball is preferably ≥95%. More preferably, the interior is loose and porous, with the internal pore size within 10 μm and the porosity ≥70%. The freeze-dried fiber is freeze-dried in situ and has a volume of 1 cm 3 ~3cm 3 , preferably the interior is loose and porous, the internal pore size is within 10um, and the porosity is ≥70%.
[0038] The application of the above-mentioned composite freeze-dried filler is characterized in that the application includes: hydrating products, dressing products and filling products.
[0039] Specifically, the mechanism and effects of the specific freeze-drying process, non-specific stabilizer, microspheres, and microsphere dispersion carrier of the present invention are as follows:
[0040] (1) The effect of the combination of silk fibroin solution and nonspecific stabilizer:
[0041] The effectiveness of silk fibroin solutions combined with nonspecific stabilizers varies depending on the specific type of stabilizer, its mechanism of action, and experimental conditions. Nonspecific stabilizers are typically used to improve solution stability and prevent protein denaturation or aggregation. They may stabilize protein structure through interactions with protein molecules, such as hydrogen bonding, electrostatic interactions, or hydrophobic interactions.
[0042] Characteristics of silk fibroin solution: Silk fibroin solution is a protein solution with excellent biocompatibility and degradability, and is widely used in the fields of tissue engineering, drug sustained-release carriers and coating materials. However, the stability of silk fibroin solution is poor and it is easily affected by environmental factors and denatured or aggregated. Since the existing freeze-dried spherical substances are all low-molecular products, low molecules are not easy to precipitate and fold, but the narrow distribution can control the molecular weight of 10kDa~80kDa, 80kDa~100kDa, 100kDa~120kDa, 120kDa~160kDa, 160kDa~200kDa, >200kDa, silk fibroin belongs to the high-molecular substance, which is prone to β-folding and is irreversible.
[0043] Diversity of combination effects: When a silk fibroin solution is used in combination with a non-specific stabilizer, the effect may vary depending on the type of stabilizer. For example, some stabilizers may significantly improve the stability of the silk fibroin solution, prolong its shelf life, and prevent it from denaturing or aggregating when the environment changes. Other stabilizers may only affect certain specific properties of the silk fibroin solution, such as viscosity and water retention.
[0044] (2) The role of microspheres and microsphere dispersion carriers
[0045] Microspheres can be used as carriers for drugs and active ingredients, enabling controlled and sustained release. By adjusting the materials and structure of the microspheres, the rate and pattern of drug release can be precisely controlled, thereby extending the duration of drug action, improving efficacy, and reducing dosing frequency and toxic side effects.
[0046] In the field of tissue engineering, microspheres can serve as three-dimensional scaffolds to support and promote cell growth and differentiation. By combining cells with microspheres, tissues or organs can be cultured in vitro, providing an effective tool for regenerative medicine. Microspheres have a high specific surface area and porous structure, making them useful in applications such as chemical adsorption, ion exchange, and dye separation. By adjusting the pore size and surface properties of the microspheres, selective adsorption and separation of specific compounds can be achieved. Microsphere dispersion carriers can also improve the physical stability of drugs. For example, by coating or adsorbing them on the drug surface, they can protect the drug from environmental factors such as light, heat, and humidity, thereby extending the drug's shelf life.
[0047] Preferably, in step S1, the molecular weight of the silk fibroin solution used is (10kDa~80kDa, 80kDa~100kDa, 100kDa~120kDa, 120kDa~160kDa, 160kDa~200kDa, >200kDa), and the test method refers to Appendix B of YY / T1950-2024 "Silk fibroin for tissue engineering medical devices", and the measured rheological data and viscosity data are imported into Favorsun SmartMolFit "complex intelligent calculation" biopolymer molecular weight calculation commercial software to calculate the number average molecular weight and weight average molecular weight.
[0048] Preferably, in step S1, the lyophilized composition liquid contains sugar substances including but not limited to trehalose, lactose, sucrose, maltose, caramel and other disaccharides.
[0049] Preferably, in step S1, the sugar alcohol substances in the freeze-dried composition liquid include but are not limited to mannitol, sorbitol, xylitol, erythritol and other sugar alcohol substances.
[0050] Preferably, in step S1, the polyol substances in the freeze-dried composition liquid include but are not limited to glycerol, ethylene glycol, butylene glycol and other polyol substances.
[0051] Preferably, in step S1, the cellulose derivative substances in the freeze-dried composition liquid include but are not limited to sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose and other cellulose derivatives.
[0052] It should be noted that not all nonspecific stabilizers can produce good compatibility with silk fibroin solutions. Therefore, when selecting a stabilizer, sufficient experimental verification and screening are required.
[0053] More preferably, in step S1, at most one of the nonspecific stabilizers is used during use, and the ratio thereof is nonspecific stabilizer 1: nonspecific stabilizer 2 = 0-1:1-3.
[0054] Preferably, in step S2, the mass ratio of microspheres: microsphere dispersing carrier (microsphere dispersing agent concentration is 1 mg / mL-40 mg / mL): purified water is 1-3:50-100:500-100. More preferably, the mass ratio is 1-1.5:50-80:800-1000.
[0055] Preferably, in step S3, when component liquid A is added to component liquid B, it is necessary to gently shake it while adding it. After it is completely added, it is placed in a refrigerator at 2-8°C for 8-24 hours to allow it to swell until it is completely dispersed. More preferably, it is 16-24 hours.
[0056] Preferably, in step S4, the method of pre-freezing the mixed solution into balls is: dropping the mixed solution into liquid nitrogen through a continuous liquid dispenser.
[0057] Preferably, the volume of the freeze-dried pellet is 15 to 45 μL, and the particle size is 1 to 5 mm, more preferably, the volume is 20 to 40 μL, and the particle size is 3.2 to 3.4 mm.
[0058] Preferably, in step S4, the method of pre-freezing the mixed solution into fibers is: dripping the mixed solution into a vial through a continuous dispenser and then placing the vial into a -18°C refrigerator for pre-cooling and forming.
[0059] Preferably, the volume of the freeze-dried fiber is 1 to 3 g, and the volume is 1 cm 3 ~3cm 3 More preferably, the volume is 1.5 to 2.5 g and the volume is 1.5 cm 3 ~2.5cm 3 .
[0060] Preferably, in step S5, the freeze-drying time is ≥30 h, the freeze-drying temperature is ≥-60° C., and the vacuum degree is ≤10 Pa.
[0061] In the present invention, "vacuum degree" refers to the gauge pressure of the freeze dryer, that is, the pressure inside the freeze dryer cabinet.
[0062] A method for preparing a controllable molecular weight silk fibroin composite freeze-dried filler, the applications of which include: hydrating products, dressing products, and filling products.
[0063] Compared with the prior art, the present invention has the following advantages:
[0064] (1) Controllable molecular weight: By precisely controlling the molecular weight of silk fibroin, the properties of the microspheres, such as particle size and porosity, can be regulated to meet different application requirements.
[0065] (2) Improved stability: The use of a specific freeze-drying procedure, non-specific stabilizers and microsphere dispersants improves the stability of the silk fibroin composite freeze-dried filler, making the microspheres more evenly dispersed and less likely to denature or aggregate during storage, transportation and use.
[0066] (3) Convenience and shelf life: This preparation method ensures the convenience of storage, transportation and use of the silk fibroin composite freeze-dried filler, and has a long shelf life.
[0067] (4) Biocompatibility and degradability: As a natural polymer material, silk fibroin has excellent biocompatibility and degradability and is suitable for use in biomedicine, tissue engineering and other fields.
[0068] (5) Structure and morphology maintenance: Through freeze-drying technology, the moisture in the microspheres can be removed while maintaining their original structure and morphology, thereby improving the stability and long-term storage performance of the microspheres.
[0069] (6) Environmental adaptability: The microspheres prepared by this method have better adaptability to environmental changes and can remain stable under different environmental conditions.
[0070] (7) Innovative freeze-drying procedure: A specific freeze-drying procedure is adopted, including multiple temperature stages and vacuum control, to optimize the freeze-drying process and improve product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 Example 1: Image of the internal pores of the silk fibroin freeze-dried ball
[0072] Figure 2 Example 1: Fourier transform infrared absorption spectrum (FT-IR) of silk fibroin freeze-dried balls
[0073] Figure 3 Example 1: X-ray diffraction (XRD) pattern of lyophilized silk fibroin pellets
[0074] Figure 4 : After the solution in Example 1 is swollen, the microspheres are dispersed.
[0075] Figure 5 : Microsphere dispersion picture in comparative example 3
[0076] Figure 6 :Silk fibroin at different concentrations promotes collagen secretion in human dermal fibroblasts
[0077] Figure 7 : Volume retention rate of short-term water light and long-term water light at different times
[0078] Figure 8 : Example 1 Animal tissue section diagram Specific implementation methods
[0080] The technical solutions of the present invention are further described below using specific examples and accompanying drawings. It should be understood that the specific examples described herein are intended solely to facilitate understanding of the present invention and are not intended to limit the present invention. Furthermore, the accompanying drawings are intended solely to better illustrate the present invention and do not limit its scope. Unless otherwise specified, the raw materials used in the examples of the present invention are commonly used in the art, and the methods used in the examples are conventional methods in the art.
[0081] Example 1:
[0082] (1) Liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa-100 kDa), 1 g of trehalose, and 0.1 g of sodium carboxymethyl cellulose were mixed by gentle shaking.
[0083] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0084] (3) Take 20g of freeze-dried liquid B and slowly add freeze-dried liquid A to liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to 100g. After all are added, place in a refrigerator at 2-8℃ to swell for 24h. The microspheres are evenly dispersed as shown in the picture. Figure 4 shown.
[0085] (4) The freeze-dried component liquid was dispersed into 30 μL drops of solution using a continuous dispenser and then dropped into liquid nitrogen for pre-cooling into balls; the pre-cooled balls were transferred together with the liquid nitrogen to a pre-cooled stainless steel tray, and then the stainless steel tray was placed in a vacuum freeze dryer that was pre-cooled (i.e., the "layer pre-cooling" program in Table 1) for freeze-drying to obtain silk fibroin freeze-dried balls with a particle size of 3.2 to 3.4 mm. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the temperature of the current process is maintained.
[0086] Table 1 Freeze-drying procedure in Example 1
[0087]
[0088]
[0089] The surface of the silk fibroin composite freeze-dried filler in Example 1 is smooth and shiny, and its internal porosity is as follows: Figure 1 As shown, the interior is loose and porous, with pores within 10 μm and a porosity of ≥70%. The lyophilized silk fibroin pellets were analyzed by FT-IR and XRD to verify whether lyophilization affects the chemical and physical structures of the silk fibroin. The chemical structure was characterized and analyzed by infrared spectroscopy (e.g. Figure 2 As shown), the FT-IR spectrum of silk fibroin is measured at 1620.39 cm -1 , 1512.88cm -1 , and 1232.77cm -1 There are characteristic peaks at the amide I band, amide II band and amide III band of silk fibroin, respectively; the physical structure of the silk fibroin freeze-dried ball was characterized and analyzed by XRD (such as Figure 3As shown in Figure 2, silk fibroin aggregates can be classified into two types: crystalline and amorphous. The crystalline forms are α- and β-types, also known as Silk I and Silk II. X-ray diffraction (XRD) patterns at 2θ = 20° indicate the Silk II crystalline structure. This indicates that the freeze-drying process does not damage the physical and chemical properties of silk fibroin, effectively preserving it.
[0090] We also conducted animal experiments on the product of Example 1 and took tissue samples after 2 weeks to see its inflammatory effect. It can be seen that it has a low inflammatory effect ( Figure 8 ).
[0091] The overall score of the freeze-dried pellets is 5. The scores for each item are shown in Table 2. The scoring criteria are detailed in Table 12.
[0092] Table 2: Example 1 Freeze-dried Ball Scoring Table
[0093]
[0094] Example 2:
[0095] (1) Liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa-100 kDa), 1 g of trehalose, and 0.1 g of sodium carboxymethyl cellulose were mixed by gentle shaking.
[0096] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0097] (3) Take 20g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Shake gently after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 24 hours.
[0098] (4) The freeze-dried component liquid was dispersed into 30 μL drops of solution using a continuous dispenser and then dropped into liquid nitrogen for pre-cooling into balls; the pre-cooled balls were transferred together with the liquid nitrogen to a pre-cooled stainless steel tray, and then the stainless steel tray was placed in a vacuum freeze dryer that was pre-cooled (i.e., the "layer pre-cooling" program in Table 1) for freeze-drying to obtain silk fibroin freeze-dried balls with a particle size of 3.2 to 3.4 mm. The detailed freeze-drying steps are listed in Table 3. In Table 3, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the current process temperature is maintained.
[0099] Table 3 Freeze-drying procedure in Example 2
[0100]
[0101]
[0102] The overall score of the freeze-dried pellets was 4.75. The scores for each item are shown in Table 4. The scoring criteria are detailed in Table 12.
[0103] Table 4: Example 2 Freeze-Dried Ball Scoring Table
[0104]
[0105] Example 3:
[0106] (1) Liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa-100 kDa), 1 g of trehalose, and 0.1 g of sodium carboxymethyl cellulose were mixed by gentle shaking.
[0107] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0108] (3) Take 25 g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the balance to 100 g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 18 hours.
[0109] (4) Disperse 2 g of the freeze-dried component liquid into a vial through a continuous dispenser for pre-cooling and molding; the pre-cooling molding method is to place the vial with the freeze-dried component liquid into a -18°C refrigerator for pre-cooling and molding. Then, the pre-cooled molded product is placed in a vacuum freeze dryer that has been pre-cooled (i.e., the "layer pre-cooling" program in Table 1) to obtain freeze-dried silk fibroin fiber. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the current process temperature is maintained.
[0110] The overall score of freeze-dried fiber is 4.25. The scores of each item are shown in Table 5. The scoring criteria are detailed in Table 12.
[0111] Table 5: Example 3 Freeze-dried Ball Scoring Table
[0112]
[0113]
[0114] Example 4:
[0115] (1) Liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 160 kDa-200 kDa), 2 g of mannitol, and 1 g of hydroxypropyl cellulose were mixed by gentle shaking.
[0116] (2) Composition of liquid B: Add 0.05 g of polycaprolactone microspheres to the swollen 2.5 wt% sodium hyaluronate solution, mix well and set aside.
[0117] (3) Take 25 g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the balance to 100 g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 18 hours.
[0118] (4) Disperse 2 g of the freeze-dried component liquid into a vial through a continuous dispenser for pre-cooling and molding; the pre-cooling molding method is to place the vial with the freeze-dried component liquid into a -18°C refrigerator for pre-cooling and molding. Then, the pre-cooled molded product is placed in a vacuum freeze dryer that has been pre-cooled (i.e., the "layer pre-cooling" program in Table 1) to obtain freeze-dried silk fibroin fiber. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the current process temperature is maintained.
[0119] The overall score of freeze-dried fiber is 4.75. The scores of each item are shown in Table 6. The scoring criteria are detailed in Table 12.
[0120] Table 6: Example 4 Freeze-dried Ball Scoring Table
[0121]
[0122] Example 5:
[0123] (1) Liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 10 kDa to 80 kDa), 1.5 g of ethylene glycol, and 0.5 g of lactose were mixed by gentle shaking.
[0124] (2) Liquid B: Add 0.1 g of chitosan microspheres to the swollen 2.2 wt% sodium hyaluronate solution, mix well and set aside.
[0125] (3) Take 20 g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100 g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 16 hours.
[0126] (4) The freeze-dried component liquid was dispersed into 30 μL drops of solution using a continuous dispenser and then dropped into liquid nitrogen for pre-cooling into balls; the pre-cooled balls were transferred together with the liquid nitrogen to a pre-cooled stainless steel tray, and then the stainless steel tray was placed in a vacuum freeze dryer that was pre-cooled (i.e., the "layer pre-cooling" program in Table 1) for freeze-drying to obtain silk fibroin freeze-dried balls with a particle size of 3.2 to 3.4 mm. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the temperature of the current process is maintained.
[0127] The overall score of the freeze-dried pellets was 4.25. The scores for each item are shown in Table 7. The scoring criteria are detailed in Table 12.
[0128] Table 7: Example 5 Freeze-Dried Ball Scoring Table
[0129]
[0130] Example 6:
[0131] (1) Composition of solution A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa-100 kDa), 1 g of trehalose, and 0.1 g of sodium carboxymethyl cellulose. Gently shake and mix.
[0132] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0133] (3) Take 20g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Shake gently after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 24 hours.
[0134] (4) The freeze-dried component liquid was dispersed into 30 μL drops of solution using a continuous dispenser and then dropped into liquid nitrogen for pre-cooling into balls; the pre-cooled balls were transferred together with the liquid nitrogen to a pre-cooled stainless steel tray, and then the stainless steel tray was placed in a vacuum freeze dryer that was pre-cooled (i.e., the "layer pre-cooling" program in Table 8) for freeze-drying to obtain silk fibroin freeze-dried balls with a particle size of 3.2 to 3.4 mm. The detailed freeze-drying steps are listed in Table 8. In Table 8, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the current process temperature is maintained.
[0135] Table 8 Freeze-drying procedure of Example 6
[0136]
[0137] The overall score of the freeze-dried pellets was 4.5. The scores for each item are shown in Table 9. The scoring criteria are detailed in Table 12.
[0138] Table 9: Example 6 Freeze-Dried Ball Scoring Table
[0139]
[0140] Comparative Example 1:
[0141] (1) Composition liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa to 100 kDa).
[0142] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0143] (3) Take 20 g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100 g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 16 hours.
[0144] (4) The freeze-dried component liquid was dispersed into 30 μL drops of solution using a continuous dispenser and then dropped into liquid nitrogen for pre-cooling into balls; the pre-cooled balls were transferred together with the liquid nitrogen to a pre-cooled stainless steel tray, and then the stainless steel tray was placed in a vacuum freeze dryer that was pre-cooled (i.e., the "layer pre-cooling" program in Table 1) for freeze-drying to obtain silk fibroin freeze-dried balls with a particle size of 3.2 to 3.4 mm. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the temperature of the current process is maintained.
[0145] There is no comprehensive score for freeze-dried pellets. The reasons are shown in Table 10. The scoring criteria are detailed in Table 12.
[0146] Table 10: Comparative Example 1 Freeze-Dried Ball Scoring Table
[0147]
[0148] Comparative Example 2:
[0149] (1) Composition liquid A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa to 100 kDa).
[0150] (2) Liquid B: Add 0.1 g of hydroxyapatite microspheres to the swollen 2.5 wt% sodium hyaluronate solution and mix well for later use.
[0151] (3) Take 20 g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Slightly shake after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100 g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 16 hours.
[0152] (4) Disperse 2 g of the freeze-dried component liquid into a vial through a continuous dispenser for pre-cooling and molding; the pre-cooling molding method is to place the vial with the freeze-dried component liquid into a -18°C refrigerator for pre-cooling and molding. Then, the pre-cooled molded product is placed in a vacuum freeze dryer that has been pre-cooled (i.e., the "layer pre-cooling" program in Table 1) to obtain freeze-dried silk fibroin fiber. The detailed freeze-drying steps are listed in Table 1. In Table 1, the temperature change rate of each step refers to the temperature change rate from the previous process to the current process, and the working hours of each step are based on the time the current process temperature is maintained.
[0153] There is no comprehensive score yet. The scores for each item are shown in Table 11, and the scoring criteria are detailed in Table 12.
[0154] Table 11: Example 3 Freeze-dried Ball Scoring Table
[0155]
[0156] Comparative Example 3:
[0157] (1) Composition of solution A: 66.67 g of 4.5 wt% silk fibroin solution (silk fibroin molecular weight 80 kDa-100 kDa), 1 g of trehalose, and 0.1 g of sodium carboxymethyl cellulose. Gently shake and mix.
[0158] (2) Liquid B: 0.1 g of hydroxyapatite microspheres, and the remainder is balanced to 100 g with purified water. After balancing, mix well and set aside.
[0159] (3) Take 20g of freeze-dried component liquid B and slowly add freeze-dried component A to component liquid B several times. Shake gently after each addition to avoid precipitation of silk fibroin. Finally, add purified water to make the final balance to 100g. After all the additions are made, place in a refrigerator at 2-8°C to swell for 24 hours.
[0160] After the preparation, the microspheres were unevenly dispersed. No freeze-drying or drip freeze-drying was performed. The microspheres were unevenly dispersed. Figure 5 As shown.
[0161] Table 12 Evaluation table of silk fibroin freeze-dried balls
[0162]
[0163]
[0164] Note:
[0165] 1. Reconstitution Time: Lyophilized pellets are the time required for 33 silk fibroin pellets to completely dissolve in 1 ml of purified water or 1 ml of normal saline. Lyophilized fiber is the time required to dissolve the lyophilized product in 1 ml of purified water or 1 ml of normal saline directly into a vial.
[0166] 2. Accelerated stability: Silk fibroin may degrade over time, causing changes in pH. The higher the degree of degradation, the greater the pH change. Accelerated stability testing is conducted at temperatures and humidity levels in accordance with the requirements of YY / T0681.1-2018. Ten days of accelerated aging is equivalent to 105 days of storage at room temperature.
[0167] Table 13 Summary of humidity of silk fibroin freeze-dried products leaving warehouse
[0168]
[0169]
[0170] Note: The humidity of the freeze-dried ball out of the warehouse is the water content inside the freeze-dried ball at time 0 when it leaves the warehouse, measured by Karl Fischer method.
[0171] Table 14: Summary of reconstitution time for lyophilized silk fibroin products
[0172] Group Reconstitution time Example 1 15s Example 2 19s Example 3 21s Example 4 22s Example 5 24s Example 6 23s Comparative Example 1 Cannot be completely reconstituted Comparative Example 2 Cannot be completely reconstituted Comparative Example 3 /
[0173] Table 15: pH difference of lyophilized silk fibroin products before and after aging
[0174]
[0175]
[0176] Summary: The product obtained in Example 1 is the optimal spherical freeze-dried product. Compared with Example 1 and 2, it shows that the freeze-drying temperature is lower, the time is longer, and the solubility of the protein microspheres is better. Compared with Example 1 and 3, it shows that the morphology of the freeze-dried product has a certain influence on the re-solubility. Compared with Example 1 and 4 and 5, the protein microspheres made by the use of non-specific stabilizers have better appearance, solubility and stability, but the non-specific stabilizer must be within a certain range. Too much will make the solubility of the freeze-dried product worse, and too little will not play a role in protecting the protein. As for the microsphere dispersant, too low a content of the microsphere dispersant will make the microspheres unevenly dispersed, and too high a content of the dispersant will affect the mixing and swelling time and the re-solubility of the freeze-dried product.
Claims
1. A method for preparing a composite freeze-dried filler of silk fibroin with controllable molecular weight, characterized in that: The following steps are involved: S1 mixes the silk fibroin solution and the non-specific stabilizer to prepare a composition liquid A; S2 swells the microsphere dispersion carrier and the microspheres to prepare a composition liquid B; S3 mixes the composition liquid A and the composition liquid B to obtain a freeze-dried composition liquid; S4 pre-cools and forms; S5 freeze-dries.
2. A preparation method according to claim 1, characterized in that: The steps include: S1: preparing composition liquid A: adding non-specific stabilizer to silk fibroin solutions of different molecular weights (protein concentration is 1 mg / mL-50 mg / mL) and mixing; the silk fibroin has a narrow distribution and controllable molecular weight, and the molecular weight range is preferably 10 kDa-80 kDa, 80 kDa-100 kDa, 100 kDa-120 kDa, 120 kDa-160 kDa, 160 kDa-200 kDa, >200 kDa; S2: preparing composition liquid B: adding purified water to the microsphere dispersion carrier and microspheres for swelling; S3: adding component liquid A to component liquid B to swell and mix at low temperature to prepare the freeze-dried component liquid for final use; S4: Precooling of freeze-dried composition liquid: The specific precooling method is one of S4.1 or S4.2 S4.1 Precooling into a specific shape: Precooling the prepared freeze-dried composition liquid into a specific shape; preferably, the freeze-dried composition liquid is 15 to 45 μL; preferably, the volume of the specific shape is within 5.00 mm 3 -40.00mm 3 The shape includes but is not limited to sphere, square, five-pointed star shape, and preferably sphere. S4.2 Precooling to form fibers: inject the freeze-dried composition liquid into a container, and place the container injected with the freeze-dried composition liquid into a refrigerator for precooling and forming; the amount of the freeze-dried composition liquid used is 1-3g; S5: Place the pre-cooled and formed specific shapes / fibers in a freeze dryer for freeze drying.
3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of silk fibroin to non-specific stabilizer is 1.5-8:1-3, and the non-specific stabilizer includes one or more of I, II, III, and IV, and specific examples are as follows: Ⅰ: Carbohydrates such as trehalose, lactose, sucrose, maltose, caramel; Ⅱ: Sugar alcohols such as mannitol, sorbitol, xylitol, erythritol; Ⅲ: Polyols such as glycerol, ethylene glycol, butanediol; IV: Cellulose derivatives such as sodium carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose.
4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of microspheres: microsphere dispersion carrier: purified water is 1-3: 50-100: 500-1000, and the concentration of the microsphere dispersant is preferably 1 mg / mL-40 mg / mL; the microspheres are preferably the substances shown in VII, VII: Microspheres are divided into natural polymer microspheres and synthetic polymer microspheres; Natural polymer microspheres such as starch microspheres, albumin microspheres, gelatin microspheres, chitosan; Synthetic polymer microspheres such as polylactic acid microspheres, hydroxyapatite microspheres, polycaprolactone microspheres; The preferred microsphere dispersant is the substance shown in Ⅷ: VIII: Microsphere dispersion carriers such as sodium hyaluronate, sodium hyaluronate, sodium polyglutamate.
5. The preparation method according to claim 1, characterized in that: In step S3, when component liquid A is added to component liquid B, it needs to be slightly shaken while adding. After it is completely added, it is placed in a refrigerator at 2-8° C. for 8-24 hours to swell until it is completely dispersed.
6. The preparation method according to claim 1, characterized in that: In step S4, the method of pre-cooling the freeze-dried composition liquid into a specific shape is to drop the mixed liquid into liquid nitrogen. Pre-cooling the fiber is to inject the freeze-dried composition liquid into a container, and put the container injected with the freeze-dried composition liquid into a refrigerator for pre-cooling and forming; the container is preferably a vial; the amount of the freeze-dried composition liquid is 1-3g.
7. A controllable molecular weight silk fibroin composite freeze-dried filler, prepared by the preparation method of any one of claims 1 to 7.
8. The controllable molecular weight silk fibroin composite freeze-dried filler according to claim 8, characterized in that: The freeze-dried filler is a freeze-dried product of a specific shape or freeze-dried fiber, preferably loose and porous inside, with an internal pore size of less than 10 um and a porosity of ≥70%.
9. Use of the controllable molecular weight silk fibroin composite freeze-dried ball filler obtained by the preparation method according to any one of claims 1 to 7 or the controllable molecular weight silk fibroin composite freeze-dried filler according to any one of claims 8 to 9, characterized in that: The applications include: hydrating products, dressing products and filling products.
Citation Information
Patent Citations
Gentamicin sulfate / gelatin microsphere complex-loaded silk fibroin scaffold and preparation method
CN103446617A
Preparation method of injectable sodium hyaluronate coated polylactic acid microspheres
CN116421779A
Composition containing structural protein as well as preparation method and application thereof
CN117285725A
High-dispersity injectable poly-L-lactic acid microspheres and preparation method thereof
CN117618650A
Filling agent for compounding fibroin with hydroxyapatite microspheres for injection and preparation method of filling agent
CN118924948A
Cited By
Silk fibroin solution injection capable of forming gel in situ as well as preparation method and application of silk fibroin solution injection
CN120733118A
Silk fibroin microspheres with uniform particle size as well as preparation method and application of silk fibroin microspheres
CN121021874A